EDUKASI SMART PARENTING BAGI ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK DI ERA MILENIAL - Andris Noya; Willyu N. Z. Pattikawa; Femmy Risakotta (Universitas Mataram, 2022)
The development of technology and information in the digital era has an impact on the character of children, both positive and negative. The negative impact caused resulted in moral degradation. Efforts that can be made to overcome this problem are the formation of children's character in a good direction. Character formation is a conscious and planned effort of teachers and parents to educate and empower the potential of children to build character so that they become useful individuals. This community service activity aims to educate teachers and parents about the importance of smart parenting in shaping children's character in the millennial era. This activity was held at Rafflesia Arnoldy PAUD, Ambon City. This activity is aimed at teachers and parents of students. In its implementation, this PKM Community Service activity includes three stages, namely the observation stage, material preparation, and training implementation. The assessment of the achievement of the participants' cognitive understanding was carried out through pre-test and post-test. The education provided to teachers and parents at Rafflesia Arnoldy PAUD regarding smart parenting in the formation of children's character in the millennial era can increase the understanding of teachers and parents. This Community Service Activity (PKM) makes a positive contribution to increasing the (cognitive) understanding of teachers and parents about the types of parenting and understanding the child's personality type. Through the education provided about temperament and parenting patterns, the understanding of teachers and parents about temperament and parenting patterns increases.